2021
DOI: 10.1177/1535370221994086
|View full text |Cite
|
Sign up to set email alerts
|

WNT signaling in atrial fibrillation

Abstract: The Wnt signaling pathway regulates physiological processes such as cell proliferation and differentiation, cell fate decisions, and stem cell maintenance and, thus, plays essential roles in embryonic development, but also in adult tissue homeostasis and repair. The Wnt signaling pathway has been associated with heart development and repair and has been shown to be crucially involved in proliferation and differentiation of progenitor cells into cardiomyocytes. The investigation of the role of the Wnt signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 91 publications
(132 reference statements)
2
11
0
Order By: Relevance
“…Moreover, our study found that despite the upregulation of the expression of FRZB in the heart tissue of patients with HF and AF, the gene expression of β-catenin downstream of the Wnt pathway was still upregulated. A similar phenomenon was also found in a previous study [ 28 ]. Wolke et al [ 28 ] considered that the up-regulation of FRZB cuts off any potentially harmful signal factor input through the Wnt pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our study found that despite the upregulation of the expression of FRZB in the heart tissue of patients with HF and AF, the gene expression of β-catenin downstream of the Wnt pathway was still upregulated. A similar phenomenon was also found in a previous study [ 28 ]. Wolke et al [ 28 ] considered that the up-regulation of FRZB cuts off any potentially harmful signal factor input through the Wnt pathway.…”
Section: Discussionsupporting
confidence: 91%
“…However, miR-200b-3p was upregulated in serum only at baseline and at 12 months. Targets of miR-200b-3p are involved in Wnt signaling pathway, whose dysregulation is known to contribute to the development of AF (Wolke et al, 2021). On the other hand, miR-34a-5p was upregulated at 12 and 24 months, while miR-125b-5p was downregulated at baseline.…”
Section: Mirnas As Biomarkers In Afmentioning
confidence: 99%
“…Double GSK3 deletion is associated with mitotic catastrophe, ventricular dysfunction and immoderate cardiac remodeling, finally leading to lethal DCM [ 80 ]. Notably, WNT signaling has been documented to hand out to atrial fibrosis as a hallmark of architectural remodeling during atrial fibrillation [ 81 ]. WNT3a, except for WNT5a, has been revealed to switch on WNT/beta-catenin signaling by expressing the profibrotic target genes within cardiac fibroblasts [ 82 ].…”
Section: Network Of Interactions Between Signaling Pathwaysmentioning
confidence: 99%